Modifikasi Aplikasi Unsur Hara untuk Perbaikan Vigorasi Bibit Padi dalam Cekaman Terendam - Rujito Agus Suwignyo; Andi Wijaya; Hesty Sihombing; Gribaldi Gribaldi (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2012)
Suwignyo et al., 2012. Modification of Nutrient Application for the Improvement of Rice Seed Vigor in Submergence Threat. JLSO 1(1):1-11.In fresh water swamp rice cultivation, farmers  face the problem of high water levels during the early stage of plant growth, causing risky situation for seed. This study was aimed to obtain a method to increase rice seedling tolerance to submergence stress through improving fertilizer application  rice variety. The experimental design used was factorial completely randomized design with three replications. The factor consists of rice varieties (Inpara 3, Inpara 4, Inpara 5, BR 11 sub-1, IR 42, Rutti, Uffa, and Serendah Kuning), and fertilization treatment (NPK at planting without submergence; NPK with N at 7 days prior to submergence; NPK with N at one day after submergence; NPK + manure with N at 7 days prior to submergence; NPK + Manure + Si + Zn with N at 7 days prior to submergence; and NPK + Manure + Si + Zn with N at one day after submergence). The results showed that application of the proper nutrients could increase rice seedling vigor under submergence stress. At nursery stage, application of NPK, Manure, Si and Zn, with Nitrogen  after submergence would improve seedling vigor after recovery period. Submergence stress tolerant varieties showed higher ability to survive under submergence stress, and Inpara 4, Inpara 5, and BR11 Sub-1 performed better than Inpara 3. Serendah Kuning showed  better response to submergence stress than other local varieties.